2020
DOI: 10.1016/j.virol.2019.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the interferon response increase the replication of gorilla simian foamy viruses

Abstract: 13Simian foamy viruses (SFVs) are complex retroviruses widespread throughout nonhuman 14 primates. SFVs can also be transmitted to humans, mostly through bites. We previously observed 15 that the primary zoonotic gorilla SFV strains much more slowly than laboratory-adapted chimpanzee 16strains. Here, we tested the hypothesis that SFV growth is limited by interferon (IFN)-induced 17 restriction factors using inhibitors of cellular signaling pathways involved in type I IFN induction or 18 action. Inhibitors of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Our own results also supported the inhibition of various FVs by IFN-β, but not by the ISG product MX2 [124]. Additionally, a new study suggested that pharmacological inhibitors of the IFN-I response enhance the replication of primary gorilla SFVs [125]. Very recently, using a myeloid cell model, the innate sensing pathways involved in FV infection were described [88].…”
Section: Innate Immune Sensing Of Foamy Virusessupporting
confidence: 76%
“…Our own results also supported the inhibition of various FVs by IFN-β, but not by the ISG product MX2 [124]. Additionally, a new study suggested that pharmacological inhibitors of the IFN-I response enhance the replication of primary gorilla SFVs [125]. Very recently, using a myeloid cell model, the innate sensing pathways involved in FV infection were described [88].…”
Section: Innate Immune Sensing Of Foamy Virusessupporting
confidence: 76%
“…Two cell lines, one epithelial (BHK-21) and one fibroblastic (HT1080), with the highest susceptibility to primary zoonotic gorilla SFV were used as virus-transmitter cells [ 49 ]. They were infected at a low moi for a short period of time to minimize viral particle release associated with CPE.…”
Section: Resultsmentioning
confidence: 99%
“…Transmitter cells (BHK-21 or HT1080) were seeded (10 5 cells/25 cm 2 flasks) and infected the following day at a multiplicity of infection (moi) of 0.05. Ruxolitinib (5 μM) was added to gorilla SFV -infected cultures [ 49 ]. At 72 h post-infection, SFV-infected cells were seeded in 96-well plates (5 x 10 3 /well) in triplicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with FV envelope (Env)-HS-PG interactions playing an important role in the early phases of FV replication is the observation that cationic polymers like polybrene or protamine sulfate, which are commonly used to enhance cell-free infection of many viruses, do not enhance or even slightly inhibit prototype FV (PFV) Env-mediated infection of target cells. 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Introductionmentioning
confidence: 99%